5-Substituted-benzylsulfanyl-thiophene-2-sulfonamides with effective carbonic anhydrase inhibitory activity: Solution and crystallographic investigations. Issue 3 (1st February 2017) - Ivanova, Jekaterīna; Balode, Agnese; Žalubovskis, Raivis; Leitans, Janis; Kazaks, Andris; Vullo, Daniela; Tars, Kaspars; Supuran, Claudiu T.
Graphical abstract: Abstract: A series of 5-substituted-benzylsulfanyl-thiophene-2-sulfonamides was prepared by reacting 5-bromo-thiophene-2-sulfonamide with 5-substituted-benzyl mercaptans. The new compounds were investigated as carbonic anhydrase (CA, EC 4.2.1.1) inhibitors. The cytosolic human (h) isoforms hCA I was poorly inhibited by the new sulfonamides (KI s in the range of 683–4250 nM), whereas hCA II, and the transmembrane, tumor associated isoforms hCA IX and XII were effectively inhibited in the subnanomolar–nanomolar range. A high resolution X-ray crystal structure of the adduct of hCA II with one of the new sulfonamides allowed us to rationalize the excellent inhibitory activity of these heterocyclic sulfonamides.